A Cross-Cultural Study of Explicit and Implicit Motivation for Long-Term Volunteering. (April 2016) - Aydinli, Arzu; Bender, Michael; Chasiotis, Athanasios; van de Vijver, Fons J. R.; Cemalcilar, Zeynep; Chong, Alice; Yue, Xiaodong
We propose a model of volunteering and test its validity across four cultural groups. We hypothesize that individuals' explicit prosocial motivation relates positively to sustained volunteering, which is conceptualized as a latent factor comprising activity as a volunteer, service length, service frequency, and hours of volunteering. Moreover, we introduced implicit prosocial motivation and hypothesized that the relationship between explicit prosocial motivation and sustained volunteering would be amplified by implicit prosocial motivation. Data were collected from samples in China, Germany, Turkey, and the United States. Results confirmed our expectation that, across cultures, sustained volunteering was associated with explicit prosocial motivation and that the relationship between explicit prosocial motivation and sustained volunteering was strongest when implicit prosocial motivation was also high. By including implicit prosocial motivation, our study offers a novel approach to identifying sustained volunteer involvement, which can be of particular relevance for recruitment activities of voluntary organizations across various cultural contexts.